Open and Positive Attitudes toward Teaching. (June 2014) - Hsu, Chia‐Fang (Sandy)
Abstract : This chapter argues that the most important thing for a nonnative English‐speaking teacher is to have an open and positive attitude toward students. A teacher's willingness to work out problems with individual students, coupled with openness to students' ideas and criticism, should help improve students' negative attitudes toward the teacher, which, in turn, should result in better learning outcomes and teaching evaluations.